Challenges faced by students in online English courses during the COVID-19 pandemic - Susiani, Ketut; Dantes, Nyoman; Arnyana, Ida Bagus Putu; Suarni, Ni Ketut; Suranata, Kadek; Suartama, I Kadek; Simamora, Alexander Hamonangan (Intelektual Pustaka Media Utama, 2024)
Online learning is a growing trend in education during the corona virus disease (COVID-19) pandemic. The purpose of this study is to ascertain the difficulties that online majors in non-English languages have when attempting to acquire English. The subject of this study involved using the questionnaire method for as many as 412 students and interviewing 15 students with a total of 17 questions. The results of this study indicate that there are several challenges faced by students during online learning; i) less familiarity with online learning as shown by 31% of students agreeing that online learning is a new learning method, ii) psychologically 30% of students choose strongly agree that they have limited opportunities to interact directly and freely with lecturers as well as with students, iii) limited facilities and infrastructure as much as 28% agree that the budget is limited to get quota or internet credit, and iv) limited internet access as many as 35% of students do not have good internet coverage to take online lectures. The findings of this study should be a reference for English lecturers to continue learning to innovate in providing online English learning by considering the existing challenges.